2008 IEEE Antennas and Propagation Society International Symposium 2008
DOI: 10.1109/aps.2008.4619161
|View full text |Cite
|
Sign up to set email alerts
|

A 60GHz line-of-sight 2x2 MIMO link operating at 1.2Gbps

Abstract: We report first experimental results from a hardware prototype of a millimeter wave lineof-sight (LOS) 2x2 MIMO link. The proposed architecture uses antenna element spacing derived from the principles of diffraction limited optics to establish multiple parallel data channels. Operation at millimeter wave carrier frequencies reduces the antenna array size to reasonable dimensions. The proposed system architecture is scalable to larger one dimensional and two dimensional arrays supporting data rates >160Gbps. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 2 publications
(2 reference statements)
0
24
0
Order By: Relevance
“…However, post processing can be applied for parallelization or equalization of the transmitted signals. Works in [10], [11] have shown that analog components like delay lines or phase shifters are capable to create an analog equalizing network that mixes received copies from different antennas and reconstructs the transmitted signals correspondingly. Due to the fact that the sub-channels are deterministic channels, the equalizing networks aiming at creating independent parallel channels have not to be adaptive.…”
Section: Introductionmentioning
confidence: 99%
“…However, post processing can be applied for parallelization or equalization of the transmitted signals. Works in [10], [11] have shown that analog components like delay lines or phase shifters are capable to create an analog equalizing network that mixes received copies from different antennas and reconstructs the transmitted signals correspondingly. Due to the fact that the sub-channels are deterministic channels, the equalizing networks aiming at creating independent parallel channels have not to be adaptive.…”
Section: Introductionmentioning
confidence: 99%
“…However, when transmit and receive antennas are suitably spaced, it has become known that the MIMO technique can be applied in a LoS environment [3]. Furthermore, theoretical studies have provided the opportunity to analyze the LoS MIMO performance [4], [5] and 10 GHz/60 GHz band H/W prototypes probe the possibility of this technique [6], [7]. However, studies on the variations in signal-to-interference ratio (SIR) by antenna spacing and an amplitude mismatch are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of using MIMO at mm-wave bands is that by having a proper inter-element spacing in both transmitting and receiving antennas, multiple independent streams, and thus high capacity, can be obtained, even in LOS [5]. Different LOS MIMO systems have been proposed and tested indoor [6] and outdoor [7,8]. Another unique characteristic of mmwave band communications is that highly directional beams can be obtained using relatively small antennas.…”
Section: Introductionmentioning
confidence: 99%